Compressive Strength of Stabilised Soil Blocks (SSBs) Produced in Eldoret Municipality of Uasin Gishu County, Kenya - Keter , J. K; Murgor , T. (African Journal of Education,Science and Technology (AJEST), 2019)
The availability of varying soil types in most parts of Kenya suggests that, SSBs technology can be feasible in most parts of the country. However, despite this overwhelming and glairing evidence of existing untapped resource, tests in alternative low cost housing material such as SSB Technology has not been carried out extensively especially in Uasin Gishu County. The main objective of this study was to determine the compressive strength of SSBs produced from the research area. Soil samples were obtained from 5 development zones namely Kimumu, Langas, King’ong’o, Munyaka and Rehema estates which are considered as low income settlement areas within the municipality. The findings from compressive strength of SSBs differed significantly (c2 = 506, df =4 p=0.00) for all cement: soil ratio groups. Strength of SSBs increases linearly with the increase in cement ratio. A ratio of 6% cement gives structurally sound blocks in Eldoret.